2017
DOI: 10.1038/s41598-017-02442-4
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics biomarkers to predict acamprosate treatment response in alcohol-dependent subjects

Abstract: Precision medicine for alcohol use disorder (AUD) allows optimal treatment of the right patient with the right drug at the right time. Here, we generated multivariable models incorporating clinical information and serum metabolite levels to predict acamprosate treatment response. The sample of 120 patients was randomly split into a training set (n = 80) and test set (n = 40) five independent times. Treatment response was defined as complete abstinence (no alcohol consumption during 3 months of acamprosate trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 42 publications
1
31
0
Order By: Relevance
“…However, even in these cases peripheral changes in metabolite concentrations can serve as important biomarkers. For example, there is preliminary evidence that serum metabolite concentrations could be used to predict acamprosate treatment outcomes although the mechanisms of action are based on the central neurotransmitter affinity (Hinton et al, 2017;Nam et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, even in these cases peripheral changes in metabolite concentrations can serve as important biomarkers. For example, there is preliminary evidence that serum metabolite concentrations could be used to predict acamprosate treatment outcomes although the mechanisms of action are based on the central neurotransmitter affinity (Hinton et al, 2017;Nam et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Glmnet, especially LASSO, has also been used in various metabolomics studies. For instance, this method has been used to predict the acamprosate treatment response in alcohol-dependent subjects based on metabolomics profile and clinical data 26 , and the age and sex of participants of the Karlsruhe Metabolomics and Nutrition (KarMeN) study based on their metabolomic profile 27 . To the best of our knowledge, this is the first report using elastic net on a time-series data for metabolomics analysis.…”
Section: Discussionmentioning
confidence: 99%
“…“In the case of acamprosate, one study (Nam et al, 2015) suggests that elevated baseline serum glutamate levels are associated with a positive response to acamprosate and might serve as a biomarker predicting efficacy,” he said. “Hinton et al (2017) observed that levels of six metabolites (glutamate, ammonia, 1‐methylhistidine, taurine, aspartate and threonine) differed between responders and nonresponders to acamprosate.”
“Hopefully, signatures comprised of various biomarkers will one day optimize the pharmacological treatment of AUD and other disorders, but we are not there yet.” George Koob, Ph.D.
…”
Section: Alcoholmentioning
confidence: 99%
“…Researchers also associated a response to acamprosate with single‐nucleotide polymorphisms (SNPs) in genes that code for neurotransmitter receptors, including a GABAA receptor subunit gene and an NMDA glutamate receptor subunit gene (Hinton et al, 2017). “Recently, Ho et al (2020) reported an association between three SNPs in a gene related to serotonin levels, TSPAN5, and longer abstinence in acamprosate‐treated patients,” he said.…”
Section: Alcoholmentioning
confidence: 99%